The Effectiveness of Kinesio Taping in Reducing Pain for Chronic Low Back Pain: A Systematic Review - Edi Setiawan; Winda Ayu Surya Ningrum (Universitas Muhammadiyah Malang, 2024)
This systematic review aims to assess the effectiveness of Kinesio Taping (KT) in alleviating pain in patients with chronic low back pain (CLBP). Chronic low back pain, a widespread and debilitating condition, necessitates the exploration of effective, non-pharmacological interventions to improve patient quality of life. This review examined studies from 2014 to 2024, sourced from Scopus, Web of Science, PubMed, and Google Scholar, focusing on randomized controlled trials that utilized KT as a primary or adjunctive therapy. The findings indicate that when combined with conventional therapies, KT often leads to notable pain reduction and functional improvement in CLBP patients. However, inconsistencies across studies reveal varied outcomes, particularly concerning KT's benefits over placebo or sham taping. Factors such as application technique, duration, and patient-specific characteristics influence KT's efficacy, emphasizing the need for standardized methodologies in future research. While KT shows promise as part of a comprehensive treatment approach, further investigation with larger sample sizes and long-term follow-up is warranted to establish definitive application guidelines and confirm its role in managing CLBP.